The Eerdmans encyclopedia of early Christian art and archaeology - Finney, Paul Corby (William B. Eerdmans Publishing Company, 2017)
Splendid, monumental reference work, authoritative and lavishly illustrated. More than 400 distinguished scholars, including archaeologists, art historians, historians, epigraphers, and theologians, have written the 1,455 entries in this monumental encyclopedia—the first comprehensive reference work of its kind. From Aachen to Zurzach, Paul Corby Finney's three-volume masterwork draws on archaeological and epigraphic evidence to offer readers a basic orientation to early Christian architecture, sculpture, painting, mosaic, and portable artifacts created roughly between AD 200 and 600 in Africa, Asia, and Europe. Clear, comprehensive, and richly illustrated, this work will be an essential resource for all those interested in late antique and early Christian art, archaeology, and history.